AGM launches eco-friendly graphene dispersions. Issue 8 (August 2021) - Unknown
Abstract : UK firm Applied Graphene Materials (AGM) has launched a range of graphene nanoplatelet dispersions designed to improve the sustainability of paints, coatings and composite materials.